Medical devices: Regulation, risk classification, and open innovation - Lukas Peter; Ladislav Hájek; Petra Maresova; Martin Augustynek; Marek Penhaker (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
In the Czech Republic, the medical device industry is an important sector with a strong tradition and has high added value and perspectives in demand under changing demographic and social structures. The aim of this article is to describe and analyze the complex issues of the new European Commission Medical Device Regulation (MDR) 2017/745 from the perspective of the strategic decisions of companies that have to comply with the requirements imposed on them by the new legislation and at the same time fulfill their own business needs and goals. The legislative changes significantly affect the standards, processes, and certifications in the medical device sector. The classification system of medical devices has been revised to more appropriately reflect the possible health risks associated with use of modern high-end technology in healthcare. The requirement is to categorize each device under the highest possible risk class, which means for the medical device manufacturers to carefully review the new rules and regulations and classify their devices accordingly.
Keywords: 650; development; European Commission; market; medical devices; regulatory